2011
DOI: 10.4103/0971-5916.92639
|View full text |Cite
|
Sign up to set email alerts
|

Microbicides: A new hope for HIV prevention

Abstract: Human immunodeficiency virus (HIV), causative agent of acquired immunodeficiency syndrome (AIDS), is a global health concern. To control its transmission, safe sex has been proposed as one of the strategies. Microbicides- intravaginal/intrarectal topical formulations of anti-HIV agents have also been proposed to prevent HIV transmission. Microbicides would provide protection by directly inactivating HIV or preventing the attachment, entry or replication of HIV in susceptible target cells as well as their disse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 100 publications
(98 reference statements)
0
10
0
Order By: Relevance
“…The plant extracts or purified phytochemicals may exhibit anti-HIV activity by inhibiting virus entry/fusion, HIV-1 reverse transcriptase (RT), protease or its integrase activity [10-13]. Further, to prevent sexual transmission of HIV, microbicides with anti-HIV properties have been proposed that can be applied topically before sexual act [14]. …”
Section: Introductionmentioning
confidence: 99%
“…The plant extracts or purified phytochemicals may exhibit anti-HIV activity by inhibiting virus entry/fusion, HIV-1 reverse transcriptase (RT), protease or its integrase activity [10-13]. Further, to prevent sexual transmission of HIV, microbicides with anti-HIV properties have been proposed that can be applied topically before sexual act [14]. …”
Section: Introductionmentioning
confidence: 99%
“…The various active ingredients in the formulation have anti-microbial, anti-inflammatory, anti-HPV and anti-HIV action (Gupta and Gupta, 2011). Basant TM inhibits the growth of Neisseria gonorrhoea, including those resistant to penicillin, tetracycline, nalidixic acid and ciprofloxacin (Talwar et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…[12] Besides, latest NACO and UNAIDS estimates have revealed that approximately 2.5 million people with HIV are in in India accounting for roughly half of Asia's HIV burden. [3]…”
Section: Introductionmentioning
confidence: 99%
“…However, HIV enters the superficial layers of the squamous epithelium by diffusing across a concentration gradient (mechanism known as “transmigration”, responsible for transmission of HIV from semen to vaginal epithelial cells) and gets sequestered their surface; and later infects CD4+ helper cells, Langerhans cells, dendritic cells, macrophages, and small Ki67 negative T cells (activated cells returning to resting state) found in mucosal epithelium. [38]…”
Section: Introductionmentioning
confidence: 99%